The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/fst.27117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucose oxidase addition on the textural characteristics of wheat-maize dough and bread

Abstract: The aim of this study was to assess the effect of adding glucose oxidase (GDX) on wheat-maize dough and bread textural characteristics. Ot strengthens the importance and need of replacing wheat flour with maize flour in regions where extensive cultivation of wheat is not possible. For improving the rheological properties of bread, GDX was added to wheat and wheat-maize flours. Wheat and maize flours were used in several ratios, but the best results were obtained for (on flour basis): 80:20, 75:25, 70:30, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Bread improvers are commonly added when existing variations within the breadmaking process such as substitution of ingredients. The choice of improver type depends mainly on the bread variant that is being produced or replaced (Cauvain, 2015), for example, studies have shown that glucose oxidase has good results in crumb strength but not in dough strength (Kouassi-Koffi et al, 2019) and also the enzyme can be related with the stability of the dough and with the weakening of the proteins (Tasiguano et al, 2019). Other examples of improvers are gums and enzymes like: Veron CP, which is a cellulolytic enzyme with hemicellulose that is used for treating flours, and guar gum, which is a seed galactomannan that can serve as a source of soluble dietary fiber (Mudgil et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Bread improvers are commonly added when existing variations within the breadmaking process such as substitution of ingredients. The choice of improver type depends mainly on the bread variant that is being produced or replaced (Cauvain, 2015), for example, studies have shown that glucose oxidase has good results in crumb strength but not in dough strength (Kouassi-Koffi et al, 2019) and also the enzyme can be related with the stability of the dough and with the weakening of the proteins (Tasiguano et al, 2019). Other examples of improvers are gums and enzymes like: Veron CP, which is a cellulolytic enzyme with hemicellulose that is used for treating flours, and guar gum, which is a seed galactomannan that can serve as a source of soluble dietary fiber (Mudgil et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Bread is a food that has been consumed all over the world for thousands of years, and wheat has been used in bread (Rosell, 2011;Shah et al, 2018;Kouassi-Koffi et al, 2019). However, bread made from wheat flour contains gluten, which is not tolerated by celiac disease patients, who find it necessary to completely restrict this protein.…”
Section: Introductionmentioning
confidence: 99%
“…Previously studied enzymes to modify gluten-free baking products include proteases, transglutaminases (TGs), oxidases, and amylases; however, the last two cannot be considered protein modifications since they work with non-protein components of doughs. More specifically, glucose oxidase oxidizes the hydroxyl groups of starch molecules, whereas amylase hydrolyzes the same complex polysaccharide into simpler forms, mainly dextrins [ 50 , 80 , 81 ].…”
Section: Protein Modification In Gluten-free Doughmentioning
confidence: 99%